PENGARUH MINAT BELAJAR DAN FASILITAS BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS XI IIS PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 3 PEKANBARU - Ulfa Andrian; Sumarno Sumarno; Suarman Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to determine the influence of learning interest and learning facilities on student achievement of class XI IIS on economic subjects in SMA Negeri 3 Pekanbaru. The population in this research is the students of class XI IIS in SMA Negeri 3 Pekanbaru that is as many as 157 students and the sample of 113 students. The data collection of this research is documentation and questionnaire. The data analysis used is multiple linear regression. The results showed that the interest of learning and learning facilities have a significant effect on learning achievement. Judging from the calculation of R2 (R Square Change) obtained value of 0.643. This means that the contribution of the influence of learning interest and learning facilities on learning achievement is 64.3%, while the remaining 35,7% influenced by other factors outside research such as peer environment, family environment and so forth.Keywords: learning interest, learning facilities, and learning achievement